2014
DOI: 10.4315/0362-028x.jfp-13-472
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Salmonella enterica Typhimurium in Water Amended with Manure

Abstract: Outbreaks of Salmonella enterica have been associated with water sources. Survival of S. enterica in various environments has been studied but survival in water has rarely been attempted. In two separate experiments, we examined the survival of S. enterica Typhimurium in clean spring water at various eutrophication levels and temperatures. In the first experiment, lasting for 135 days, survival of S. enterica (10(10) CFU/ml) in water with 0, 50, 100, 500, and 1,000 mg/liter of added carbon at 7, 17, and 27°C w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The presence of S. Newport on sanitizertreated fruit tissues highlights the ability of dust transferred Salmonella to persist from blossom to fruit set (Table 2) The presence of aerosolized bacteria has been demonstrated in poultry processing facilities and farms. Soil in the farm environment could serve as the most obvious source of dust (Ravi et al, 2011, Millner, 2009, Cevallos-Cevallos et al, 2014. Smaller soil particles could be dispersed due the wind, rain and changes in humidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of S. Newport on sanitizertreated fruit tissues highlights the ability of dust transferred Salmonella to persist from blossom to fruit set (Table 2) The presence of aerosolized bacteria has been demonstrated in poultry processing facilities and farms. Soil in the farm environment could serve as the most obvious source of dust (Ravi et al, 2011, Millner, 2009, Cevallos-Cevallos et al, 2014. Smaller soil particles could be dispersed due the wind, rain and changes in humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Foodborne pathogens could associate themselves with particulate matter and can be dispersed from their source (Berry et al, 2015;Cevallos-Cevallos et al, 2014). Soil, composts and manure are suspected as sources of foodborne pathogens and studies have shown that these can be aerosolized and lead to pathogen spread (Brandl, 2006;Millner, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis of reintroduction still needs to be further tested and validated by independent studies in various geographic and ecological regions. Survival of Salmonella in the environment has been a longstanding issue ( 37 , 38 ), but survival of Salmonella in surface water has been underaddressed ( 25 , 26 ). In fact, most of the reports describing the persistence of Salmonella were related to poultry houses ( 39 , 40 ), swine and dairy farms ( 41 43 ), produce and fruit farms ( 44 46 ), and the process of adaptation and/or colonization of various hosts by Salmonella that might be involved ( 35 , 45 ), where numerous ecological factors affect the Salmonella survival niches in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, microarray analysis can also provide a quick snapshot of the genomic content of the pathogens; such information, in turn, will augment the detection, identification, and attribution of strains associated with outbreaks. Therefore, the aims of this study were 2-fold: (i) to develop and validate a DNA microarray for subtyping Salmonella enterica and (ii) to take advantage of the high discriminatory power that DNA microarray offers to investigate the 2-year predominance of Salmonella Newport in surface irrigation pond environments in the southeastern United States and to gain insight into a underaddressed issue in the field of microbiology and food safety, i.e., survival of Salmonella enterica in environmental water ( 25 , 26 ), in particular, in irrigation pond water used for produce production.…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens such as Campylobacter jejuni , Salmonella spp., and Listeria monocytogenes are known to be responsible for major food‐borne zoonotic diseases (EFSA, ) and to be excreted by farm animals that constitute a reservoir (Avrain, Humbert, Sanders, Vernozy‐Rozand, & Kempf, ; Boscher, Houard, & Denis, ; Kempf et al, ; Milnes et al, ; Patterson, Kim, Borewicz, & Isaacson, ; Tadesse et al, ; Thépault et al, ). Moreover, these pathogens can persist in manure, soil and water (Cevallos‐Cevallos, Gu, Richardson, Hu, & Bruggen, ; Erickson, Smith, Jiang, Flitcroft, & Doyle, ; Jäderlund, Sessitsch, & Arthurson, ). The fate of human and animal pathogens through the AD process is therefore of major concern.…”
Section: Introductionmentioning
confidence: 99%